Spiritual care in Slovenian nursing homes: a quantitative descriptive study - Karnjuš, Igor; Bogdan, Denis; Prosen, Mirko; Ličen, Sabina (Magyar Gerontológia, 2021)
Introduction: Spiritual care is an important component of holistic care in nursing. However, health care workers are not unanimous in who is responsible for the spiritual care of patients. It is likely that nurses are best suited to provide spiritual care because of the nature of their work, which requires constant contact with patients. Yet, meeting spiritual needs is not well defined in the role of nurses and is not always taught comprehensively in formal nursing education programmes. The aim of this study was to explore the extent to which nurses working in social care settings implement interventions related to spiritual care in their daily practise, how they perceive their knowledge of spiritual care, and the extent to which this dimension of care was included in their nursing education programmes. Methods: A non-experimental quantitative descriptive research study was used. In April 2020, 214 nurse assistants and registered nurses from 12 nursing homes in Slovenia participated in the study. The questionnaire used in the study included 12 statements related to 3 main areas: i) knowledge of the concepts of spirituality and religion, ii) implementation of spiritual/religious interventions in daily practice, iii) spirituality in nursing education. The individual statements were rated by the respondents on a 5-point Likert scale (1 - strongly disagree to 5 - strongly agree). The questionnaire had adequate internal consistency (Cronbach alpha = 0.857). Data were described using calculated means, Mann-Whitney U test, and Spearman correlation coefficient. A p-value ≤ 0.05 was considered significant. Results: Regular spiritual assessment of nursing home residents is rarely performed by nurses (x̄=2.73, s=1.03). Female nurses (U=2191.500, p=0.008) and nurses who described themselves as religious (U=3314.000, p=0.001) implement spiritual/religious interventions in daily practice to a greater extent; they also expressed higher knowledge of the concepts of spirituality and religion compared to the others (religious/non-religious: U=2920.000, p=0.000; female/male: U=1885.000, p=0.000). The implementation of spiritual/religious interventions in daily practice correlated positively and statistically significantly mainly with self-perceived knowledge of the concepts of spirituality and religion (r=0.495, p=0.000) and the extent to which the content of spiritual care was represented in their nursing education program (r=0.494, p=0.000). However, nurses emphasized that the concept of spirituality and spiritual care tended to be poorly represented in formal nursing education programs (x̄=2.76, s=0.89). Discussion and conclusions: Individual characteristics, particularly self-reported religiosity and gender, appear to have an important influence on the implementation of spiritual/religious interventions in daily practise. In addition, our study suggests that the level of knowledge about the concepts of spirituality and religion influences nurses’ willingness to implement spiritual care with their residents. Therefore, nursing educators need to develop curricula that include strategies to increase trainees’ awareness of spiritual care. Current international research efforts on perceptions of spirituality and spiritual care in nursing offer important contributions to understanding the role of nursing in relation to spirituality and to developing educational content and approaches for both undergraduate and lifelong learning in nursing.